Prevalence of abnormal ECGs in male soccer players decreases with the Seattle criteria, but is still high. Issue 4 (24th June 2014) - Berge, H. M.; Gjesdal, K.; Andersen, T. E.; Solberg, E. E.; Steine, K.
<x xml:space="preserve">Abstract</x> Electrocardiogram (ECG) and echocardiography are mandatory in preparticipation cardiac screening in soccer players. Abnormal ECG findings usually require follow‐up investigations. The main aim of this study was to compare the prevalence of abnormal ECG findings in male professional soccer players according to European Society of Cardiology's (ESC) recommendations and the Seattle criteria, and to assess the need for echocardiography. ECGs from 587 of 595 (99%) players were recorded with ClickECG, and measurements were derived with visually adjusted on‐screen calipers on the computer‐based averaged PQRST complex. Echocardiographic recordings were performed with Vivid 7/i and categorized according to reference values for athlete's heart. After the initial screening, 32 (5.5%) players were recommended for follow‐up. The prevalence of abnormal ECGs was 29.3% vs 11.2% according to the ESC's recommendations and the Seattle criteria, respectively. None of the players with abnormal ECGs only according to the ESC's recommendations had abnormal echocardiograms. Echocardiography alone detected one player with abnormalities (athlete's heart). The Seattle criteria reduced the number of athletes with abnormal ECGs considerably compared with the ESC recommendations. Based on echocardiographic evaluations, this increased the specificity of the Seattle criteria, without increasing the number of false‐negative ECGs. The need for mandatory echocardiography in soccer players seems limited.